Motivational Influences on Adult Arab Learners of English in the UAE - Al Okla, Nour (2015)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Nour Al Okla entitled, "Motivational Influences on Adult Arab Learners of English in the UAE," submitted June 2015. Thesis advisor is Dr. Sara Cotterall. Soft and hard copy available.